Comparison of Ultrasonography to MRI in the Diagnosis of Lower Extremity Bone Stress Injuries: A Prospective Cohort Study. (22nd March 2022) - Syrop, Isaac; Fukushima, Yaeko; Mullins, Kevin; Raiser, Sara; Lawley, Richard; Bosshardt, Lauren; Finlay, Andrea; Ray, Jeremiah; Fredericson, Michael
Abstract : Objective: To determine the sensitivity and specificity of ultrasound imaging (USI) compared to the reference‐standard of MRI in the diagnosis of bone stress injury (BSI). Methods: A prospective blinded cohort study was conducted. Thirty seven patients who presented to an academic sports medicine clinic from 2016 to 2020 with suspected lower‐extremity BSI on clinical exam underwent both magnetic resonance imaging (MRI) and USI. Participant characteristics were collected including age, gender and sport. Exclusion criteria included contraindication for dedicated MRI, traumatic fracture, or severe tendon or ligamentous injury. The primary outcome measure was BSI diagnosis by USI. An 8‐point assessment system was utilized on USI for diagnosis of BSI, and the Fredericson and Nattiv 22 criteria were applied to classify MRI findings. Results: Thirty seven participants who met study criteria were consented to participate. All participants completed baseline measures. Using MRI, there were 30 (81%) athletes with a positive and seven participants with a negative BSI diagnosis. The most common BSIs in the study were in the metatarsal (54%) and tibia (32%). Compared to MRI, USI demonstrated 0.80 sensitivity (95% confidence interval [CI], 0.61–0.92) and 0.71 specificity (95% CI, 0.29–0.96) in detecting BSI, with a positive predictive value of 0.92 (95% CI, 0.75–0.99) and negative predictive value of 0.45 (95% CI, 0.17–0.77). Conclusions: USI is a potentially useful point‐of‐care tool for practicing sports medicine providers to combine with their clinical evaluation in the diagnosis of BSIs. Further research is ongoing to determine the role of USI in follow‐up care and return‐to‐play protocols.